1995
DOI: 10.1128/jb.177.23.6902-6909.1995
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the gonococcal glmU gene encoding the enzyme N-acetylglucosamine 1-phosphate uridyltransferase involved in the synthesis of UDP-GlcNAc

Abstract: In searching for the gonococcal sialyltransferase gene(s), we cloned a 3.8-kb DNA fragment from gonococcus strain MS11 that hybridized with the oligonucleotide JU07, which was derived from the conserved C terminus of the sialyl motif present in mammalian sialyltransferases. Sequencing of the fragment revealed four putative open reading frames (ORFs), one of which (ORF-1) contained a partial sialyl motif including the amino acid sequence VGSKT, which is highly conserved among sialyltransferases. The gene was fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Sitedirected mutagenesis experiments further demonstrated the important role of two of the four cysteines of GlmU, namely residues Cys 307 and Cys 324 , for acetyltransferase activity (17). The GlmU protein has been shown to exhibit a number of characteristics, which suggested that the acetyltransferase and uridyltransferase activities may reside in separate catalytic domains: (i) the substrates, products, and effectors of the acetyltransferase reaction did not inhibit the uridyltransferase activity and vice versa (13,18); (ii) the intermediate GlcNAc-1-P was clearly released from the acetyltransferase domain prior to transformation by the uridyltransferase domain (18); (iii) portions of the GlmU amino acid sequence showing simi-larities with that of other previously characterized XDP-sugar pyrophosphorylase and acetyltransferase activities were located in the N-terminal portion and the second third of the protein, respectively (13,15,19); (iv) the acetyltransferase but not the uridyltransferase was shown to be inactivated by thiolspecific reagents, and the two cysteine residues whose alteration resulted in dramatic decreases of acetyltransferase activity were identified in the second moiety of the protein sequence (17); (v) mutagenesis of residues that are important for uridyltransferase activity did not affect acetyltransferase at all (Ref. 20 and data not shown); (vi) the fusion of a His 6 tag at the C terminus of the protein resulted in a 20-fold decrease of acetyltransferase activity, without change in its uridyltransferase activity (17).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Sitedirected mutagenesis experiments further demonstrated the important role of two of the four cysteines of GlmU, namely residues Cys 307 and Cys 324 , for acetyltransferase activity (17). The GlmU protein has been shown to exhibit a number of characteristics, which suggested that the acetyltransferase and uridyltransferase activities may reside in separate catalytic domains: (i) the substrates, products, and effectors of the acetyltransferase reaction did not inhibit the uridyltransferase activity and vice versa (13,18); (ii) the intermediate GlcNAc-1-P was clearly released from the acetyltransferase domain prior to transformation by the uridyltransferase domain (18); (iii) portions of the GlmU amino acid sequence showing simi-larities with that of other previously characterized XDP-sugar pyrophosphorylase and acetyltransferase activities were located in the N-terminal portion and the second third of the protein, respectively (13,15,19); (iv) the acetyltransferase but not the uridyltransferase was shown to be inactivated by thiolspecific reagents, and the two cysteine residues whose alteration resulted in dramatic decreases of acetyltransferase activity were identified in the second moiety of the protein sequence (17); (v) mutagenesis of residues that are important for uridyltransferase activity did not affect acetyltransferase at all (Ref. 20 and data not shown); (vi) the fusion of a His 6 tag at the C terminus of the protein resulted in a 20-fold decrease of acetyltransferase activity, without change in its uridyltransferase activity (17).…”
mentioning
confidence: 94%
“…We showed earlier that the two latter activities were carried by a single 456-amino acid protein, the product of a gene we named glmU located just upstream from the GlcN-6-P synthase glmS gene at 84 min on the E. coli chromosome (7,14). The glmU gene has been identified in some other bacterial species, in particular Neisseria gonorrhoeae (15) and Bacillus subtilis (16).…”
mentioning
confidence: 99%
“…45 kDa. This estimated molecular mass is slightly smaller than those of UDP-GlcNAc pyrophosphorylases from Escherichia coli (49 kDa) [5], Neisseria gonorrhoeae (49 kDa) [27] and Bacillus subtilis (50 kDa) [28]. The low molecular mass of the enzymes derived from T. caldophilus GK24 could be explained by their having more compact structures than those from mesophilic bacteria, as shown for T. thermophilus Top DNA polymerase [29].…”
Section: Resultsmentioning
confidence: 99%
“…N-terminal and internal peptide sequences of UDP-sugar pyrophosphorylase, determined by Edman degradation, The peptide sequences were analysed as described in the Materials and methods section. The enzymes and organisms are identified as follows : a, UDPsugar pyrophosphorylase from T. caldophilus GK24 ; b, c, d, UDP-GlcNAc pyrophosphorylase ; e NDP-hexose pyrophosphorylase ; f, g, h, UDP-glucose pyrophosphorylase ; b and i, E. coli [5,36] ; c, Neisseria gonorrhoeae [27] ; d, Bacillus subtilis [28] ; e, Saccharomyces cerevisiae [33] ; f, Mycoplasma pneumoniae [34] ; g, Streptococcus pneumoniae [35] ; h, Xanthomonas campestris [36]. Asterisks indicate identical amino acid residues ; full points represent similar amino acid residues.…”
Section: Peptide Sequencesmentioning
confidence: 99%
“…While the conflation of gene and protein seems unusually rife in this area, it is by no means restricted to it, nor is it restricted to plant biology. Examples abound of statements that genes "transport" substances (Dean et al 2003), "synthesize" or "produce" other substances (Malik et al 2009;Pulkkinen et al 2000;Weiner et al 1993), and "catalyze" chemical reactions Drakas et al 2005;Lewinsohn et al 2001;Metherall et al 1996;Ono et al 1999;Powell et al 2008;Ullrich and van Putten 1995).…”
mentioning
confidence: 99%